A NiMoS flower-like structure with self-assembled nanosheets as high-performance hydrodesulfurization catalysts. Issue 6 (27th January 2016) - Lai, Weikun; Chen, Zhou; Zhu, Jianping; Yang, Lefu; Zheng, Jinbao; Yi, Xiaodong; Fang, Weiping
Abstract : Nanosheet assembled NiMoS nanoflowers revealed a defect-rich structure and abundant Ni–Mo–S edge sites, which dramatically enhance the hydrodesulfurization activity of thiophene and 4, 6-DMDBT. Abstract : Uniform 3D NiMoS nanoflowers with self-assembled nanosheets were successfully synthesized via a simple hydrothermal growth method using cheap and nontoxic elemental sulfur as sulfur sources. The structure and morphology of the nanomaterials were characterized by SEM, TEM, XRD, Raman and XPS analyses, revealing that the NiMoS nanoflowers were composed of ultrathin nanosheets with a thickness of approximately 6–12 nm. The HRTEM results indicate that the curve/short MoS2 slabs on the nanosheets possess the characteristics of dislocations, distortions and discontinuity, which suggests a defect-rich structure, resulting in the exposure of additional Ni–Mo–S edge sites. The obtained NiMoS nanoflowers exhibited an excellent activity for thiophene hydrodesulfurization (HDS) and 4, 6-dimethyldibenzothiophene deep HDS due to their high density of active sites. The outstanding HDS performance suggests that these NiMoS composites with a unique flower-like nanostructure could be useful as promising catalysts for deep desulfurization of fuel oils.